Prevalence of generalized anxiety disorder among nursing students in Iran during the COVID-19 pandemic: A web-based cross-sectional study - Maryam Hasanpour; Saman Maroufizadeh; Hossein Mousavi; Fatemeh Noughani; Mojgan Afshari (International Journal of Africa Nursing Sciences, 2021)
Background: The Coronavirus disease 2019 (COVID-19) is a public health emergency that poses anxiety symptoms to nursing students (P. Li et al., 2020). Therefore, this study aimed to examine the prevalence of anxiety and its associated factors in nursing students in Iran during the COVID-19 pandemic. Methods: We performed this web-based cross-sectional study on 174 nursing students in Iran, between 4 and 24 April 2020. Data were collected through an online questionnaire using social media like Telegram and WhatsApp. Anxiety was measured via the Generalized Anxiety Disorder-7 (GAD-7). Simple and multiple logistic regression analyses were undertaken to examine independent predictors of anxiety. Statistical analysis was performed using SPSS for Windows, version 16.0. Results: The mean GAD-7 total score was 6.05 ± 4.77, and the prevalence of GAD using a cut-off value of 10 for the GAD-7 was 20.7%. According to the adjusted analysis, GAD was significantly associated with having chronic diseases (OR = 5.74, 95% CI: 1.39–23.72), long time thinking about COVID-19 (OR = 14.09, 95% CI: 4.36–45.54), and death of family members, relatives or friends due to COVID-19 (OR = 4.53, 95% CI: 1.08–18.93). Conclusion: The prevalence of GAD is considerably high in nursing students during the COVID-19 pandemic in Iran. Thus, a holistic approach, including management policies, psychosocial interventions, and training, is critical to reducing anxiety symptoms during the COVID-19 pandemic as well as during any outbreaks of other infectious diseases in the future.